Network performance optimisation using triple interleaving routing algorithm for oil and gas pipeline network. (16th February 2022) - Lee, Mohamad Yusry Lee Ikhwan; Azman, Amierul Syazrul Azril; Subramaniam, Siva Kumar; Feroz, Farah Shahnaz
As demand for oil and gas increases, demands for a safe and efficient system for remote control and pipeline management also increases. The wireless sensor network (WSN) can facilitate real-time data transmission between sensor nodes and centralised monitoring stations. In this application, nodes are distributed in a linear chain configuration to cover long-distance pipelines in the midstream. When the size of the network increases, the performance of WSN is compromised. Consequently, the network has a substantially low throughput, low delivery ratio, high latency, high energy consumption, and unfairness. In this paper, ad-hoc on-demand distance vector triple interleaving (AODVTRI), a reactive protocol that reduced routing inconsistency by splitting the network traffic into three separate routes with the consideration of x-axis is proposed. The proposed routing protocol was evaluated with AODV and DSDV with 20, 40, 60, 80, 100, 120, 140, 160, 180, and 200 node deployments in accordance with IEEE802.11 standard.